Gabriel Harvey and the History of Reading (UCL Press, 2023)
Few articles in the humanities have had the impact of Lisa Jardine and Anthony Grafton’s seminal ‘Studied for Action’ (1990), a study of the reading practices of Elizabethan polymath and prolific annotator Gabriel Harvey. Their excavation of the setting, methods and ambitions of Harvey’s encounters with his books ignited the History of Reading, an interdisciplinary field which quickly became one of the most exciting corners of the scholarly cosmos. A generation inspired by the model of Harvey fanned out across the world’s libraries and archives, seeking to reveal the many creative, unexpected and curious ways that individuals throughout history responded to texts, and how these interpretations in turn illuminate past worlds.